2022
DOI: 10.1021/acsmacrolett.2c00448
|View full text |Cite
|
Sign up to set email alerts
|

PET-RAFT Increases Uniformity in Polymer Networks

Abstract: Photoinduced electron/energy transfer (PET)-reversible addition−fragmentation chain transfer polymerization (RAFT) and conventional photoinitiated RAFT were used to synthesize polymer networks. In this study, two different metal catalysts, namely, tris[2-phenylpyridinato-C2,N]iridium(III) (Ir(ppy) 3 ) and zinc tetraphenylporphyrin (ZnTPP), were selected to generate two different catalytic pathways, one with Ir(ppy) 3 proceeding through an energytransfer pathway and one with ZnTPP proceeding through an electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…An expected difference in ESR between networks with [HDDA] 0 = 1.5 and 3 was clearly visible. However, no difference in swelling was observed for networks with [HDDA] 0 = 3 prepared at various catalyst concentrations as all samples 40 However, given the larger measurement error in networks with [HDDA] 0 = 1.5, this discrepancy is not substantial. These results were further supported by a rheological analysis of the shear storage moduli (G′) of dried networks (Figure 4b).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…An expected difference in ESR between networks with [HDDA] 0 = 1.5 and 3 was clearly visible. However, no difference in swelling was observed for networks with [HDDA] 0 = 3 prepared at various catalyst concentrations as all samples 40 However, given the larger measurement error in networks with [HDDA] 0 = 1.5, this discrepancy is not substantial. These results were further supported by a rheological analysis of the shear storage moduli (G′) of dried networks (Figure 4b).…”
mentioning
confidence: 77%
“…38 Konkolewicz and Matyjaszewski employed degradable crosslinkers to compare the structure and mechanical properties of networks prepared by ATRP and RAFT. 39,40 However, an interdependence between gelation kinetics, primary chain dispersity, and physical properties of networks from RDRP has not yet been studied.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Jin and co-workers 37,100 used PET-RAFT polymerization for 3D printing under ambient conditions and visible light. Shiwanka et al 101 demonstrated that PET-RAFT polymerization had higher potential in forming a more uniform network than conventional RAFT polymerization, which swelling ratio experiments can verify. Jianzhi et al 102 reported a bilayer hydrogel for wound dressing obtained using PET-RAFT polymerization.…”
Section: Other Applicationsmentioning
confidence: 94%
“…107 Since then zinc tetraphenylporphyrin (ZnTPP) was frequently used as metal-based photo catalyst in visible light induced PET-RAFT. 36,[114][115][116][117][118] Very recently Wanasinghe et al 116 used both Ir(ppy) 3 and ZnTPP to analyze bulk swelling ratios and homogeneity of polymer networks, whereby better results were reported using ZnTPP. Corrigan et al 119 used ZnTPP as photoredox catalyst for a PET-RAFT polymerization at low-intensity yellow light irradiation, ambient temperatures, and in an open reaction vessel in the presence of oxygen.…”
Section: Visible Light Induced Raft and Iniferter Initiated Polymeriz...mentioning
confidence: 99%